2012
DOI: 10.1103/physrevlett.108.218104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of a Microswimmer in Poiseuille Flow

Abstract: We study the three-dimensional dynamics of a spherical microswimmer in cylindrical Poiseuille flow which can be mapped onto a Hamiltonian system. Swinging and tumbling trajectories are identified. In 2D they are equivalent to oscillating and circling solutions of a mathematical pendulum. Hydrodynamic interactions between the swimmer and confining channel walls lead to dissipative dynamics and result in stable trajectories, different for pullers and pushers. We demonstrate this behavior in the dipole approximat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
325
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(344 citation statements)
references
References 24 publications
19
325
0
Order By: Relevance
“…These theories predict a negative value for the coefficient K for pushers at low shear rates, meaning the suspension can exhibit a lower viscosity than the suspending fluid. The theoretical assessment of shear viscosity relies on an assumed statistical representation of the orientations of the bacteria, captured by a Fokker-Plank equation and a kinematic model for the swimming trajectories [25,26].Despite the large number of theoretical studies, few experiments have been conducted. With bacillus subtilis (pushers) trapped in a soap film Sokolov et al[12] have shown that a vorticity decay rate could be associated with a strong decrease of shear viscosity in the presence of bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These theories predict a negative value for the coefficient K for pushers at low shear rates, meaning the suspension can exhibit a lower viscosity than the suspending fluid. The theoretical assessment of shear viscosity relies on an assumed statistical representation of the orientations of the bacteria, captured by a Fokker-Plank equation and a kinematic model for the swimming trajectories [25,26].Despite the large number of theoretical studies, few experiments have been conducted. With bacillus subtilis (pushers) trapped in a soap film Sokolov et al[12] have shown that a vorticity decay rate could be associated with a strong decrease of shear viscosity in the presence of bacteria.…”
mentioning
confidence: 99%
“…These theories predict a negative value for the coefficient K for pushers at low shear rates, meaning the suspension can exhibit a lower viscosity than the suspending fluid. The theoretical assessment of shear viscosity relies on an assumed statistical representation of the orientations of the bacteria, captured by a Fokker-Plank equation and a kinematic model for the swimming trajectories [25,26].…”
mentioning
confidence: 99%
“…We propose a detailed quantitative description of the experimental dynamics and stationary regimes of what we call photofocusing [9] coupled to an analytical and numerical treatment of the problem in a spirit similar to [10,11].…”
mentioning
confidence: 99%
“…Their collective motion drives macroscopic fluid flow as in bioconvection [11] or vortex formation [12]. Hydrodynamic interactions between microswimmers crucially determine their collective patterns [13][14][15][16][17][18][19][20], while external fluid flow leads to aggregation [21], trapping [22], and nonlinear swimming dynamics [23].…”
mentioning
confidence: 99%